Pregunta
upstudy study bank question image url

\( q(x)=2+x-2 x^{2}-x^{3}, x \in \mathbb{R} \), is a cubic function. (a) Find each of the following: (i) \( q(-1) \) (ii) \( q^{\prime}(x) \) (iii) \( q^{\prime}(-1) \) b) \( y=q(x), x \in \mathbb{R} \), is a graph of \( q(x) \). (i) Show that \( (1,0) \) is a point on the graph of \( q(x) \). (ii) Find the slope of the tangent to \( y=q(x) \) at the point \( (1,0) \). (iii) Hence, find the equation of the tangent to \( y=q(x) \) at \( (1,0) \). Give your answer in the form \( a x+b y+c=0 \). [Hint: use \( y-y_{1}=m\left(x-x_{1}\right) \) ]

Ask by Wade Maxwell. in Ireland
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

**Simplified Answers:** a) i) \( q(-1) = 0 \) ii) \( q^{\prime}(x) = -3x^{2} - 4x + 1 \) iii) \( q^{\prime}(-1) = 2 \) b) i) \( (1, 0) \) is a point on the graph of \( q(x) \). ii) The slope of the tangent at \( (1, 0) \) is \( -6 \). iii) The equation of the tangent at \( (1, 0) \) is \( 6x + y - 6 = 0 \).

Solución

Let's analyze the cubic function \( q(x) = 2 + x - 2x^{2} - x^{3} \) and address each part of the problem step by step. --- ## **a) Calculations Involving \( q(x) \)** ### **i) Find \( q(-1) \)** To find \( q(-1) \), substitute \( x = -1 \) into the function: \[ \begin{align*} q(-1) &= 2 + (-1) - 2(-1)^{2} - (-1)^{3} \\ &= 2 - 1 - 2(1) - (-1) \\ &= 2 - 1 - 2 + 1 \\ &= (2 - 1) + (-2 + 1) \\ &= 1 - 1 \\ &= 0 \end{align*} \] **Answer:** \( q(-1) = 0 \) --- ### **ii) Find \( q^{\prime}(x) \)** To find the derivative \( q^{\prime}(x) \), differentiate \( q(x) \) with respect to \( x \): \[ \begin{align*} q(x) &= 2 + x - 2x^{2} - x^{3} \\ q^{\prime}(x) &= \frac{d}{dx}(2) + \frac{d}{dx}(x) - \frac{d}{dx}(2x^{2}) - \frac{d}{dx}(x^{3}) \\ &= 0 + 1 - 4x - 3x^{2} \\ &= -3x^{2} - 4x + 1 \end{align*} \] **Answer:** \( q^{\prime}(x) = -3x^{2} - 4x + 1 \) --- ### **iii) Find \( q^{\prime}(-1) \)** Using the derivative found in part (ii), substitute \( x = -1 \): \[ \begin{align*} q^{\prime}(-1) &= -3(-1)^{2} - 4(-1) + 1 \\ &= -3(1) + 4 + 1 \\ &= -3 + 4 + 1 \\ &= 2 \end{align*} \] **Answer:** \( q^{\prime}(-1) = 2 \) --- ## **b) Graph Analysis of \( y = q(x) \)** ### **i) Show that \( (1, 0) \) is a Point on the Graph of \( q(x) \)** To verify that \( (1, 0) \) lies on the graph of \( q(x) \), substitute \( x = 1 \) into \( q(x) \) and check if \( y = 0 \). \[ \begin{align*} q(1) &= 2 + (1) - 2(1)^{2} - (1)^{3} \\ &= 2 + 1 - 2(1) - 1 \\ &= 2 + 1 - 2 - 1 \\ &= (2 + 1) + (-2 -1) \\ &= 3 - 3 \\ &= 0 \end{align*} \] Since \( q(1) = 0 \), the point \( (1, 0) \) lies on the graph of \( q(x) \). **Answer:** \( (1, 0) \) is a point on the graph of \( q(x) \). --- ### **ii) Find the Slope of the Tangent to \( y = q(x) \) at \( (1, 0) \)** The slope of the tangent at a point \( x = a \) is given by the derivative \( q^{\prime}(a) \). From part **a(ii)**, we have: \[ q^{\prime}(x) = -3x^{2} - 4x + 1 \] Substitute \( x = 1 \): \[ \begin{align*} q^{\prime}(1) &= -3(1)^{2} - 4(1) + 1 \\ &= -3 - 4 + 1 \\ &= -6 \end{align*} \] **Answer:** The slope of the tangent at \( (1, 0) \) is \( m = -6 \). --- ### **iii) Find the Equation of the Tangent to \( y = q(x) \) at \( (1, 0) \)** We can use the point-slope form of a line: \[ y - y_{1} = m(x - x_{1}) \] Where: - \( m \) is the slope - \( (x_{1}, y_{1}) \) is the point on the line Given: - \( m = -6 \) - \( (x_{1}, y_{1}) = (1, 0) \) Substitute these values: \[ \begin{align*} y - 0 &= -6(x - 1) \\ y &= -6x + 6 \end{align*} \] To express this in the form \( a x + b y + c = 0 \), rearrange the equation: \[ \begin{align*} y &= -6x + 6 \\ 6x + y - 6 &= 0 \end{align*} \] **Answer:** An equation for the tangent is \( 6x + y - 6 = 0 \). ---

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve your cubic function challenge, let's dive into each part step by step! First, calculating \( q(-1) \): Substituting \(-1\) into the function gives: \[ q(-1) = 2 + (-1) - 2(-1)^2 - (-1)^3 = 2 - 1 - 2 + 1 = 0 \] Now, let's find the derivative \( q^{\prime}(x) \): To differentiate the function, we get: \[ q^{\prime}(x) = 0 + 1 - 4x - 3x^2 = 1 - 4x - 3x^2 \] Next, we evaluate \( q^{\prime}(-1) \): Substituting \(-1\) into the derivative gives: \[ q^{\prime}(-1) = 1 - 4(-1) - 3(-1)^2 = 1 + 4 - 3 = 2 \] Now, moving onto part (b), we want to show that \((1,0)\) is a point on the graph of \( q(x) \): Calculating: \[ q(1) = 2 + 1 - 2(1)^2 - (1)^3 = 2 + 1 - 2 - 1 = 0 \] Thus, the point \((1,0)\) is indeed on the graph! To find the slope of the tangent at \((1,0)\): We already found that \( q^{\prime}(1) \) is: \[ q^{\prime}(1) = 1 - 4(1) - 3(1)^2 = 1 - 4 - 3 = -6 \] Lastly, we need the equation of the tangent line in the form \( ax + by + c = 0 \): Using the point-slope form \( y - y_1 = m(x - x_1) \): \[ y - 0 = -6(x - 1) \] Simplifying gives: \[ y = -6x + 6 \\ 6x + y - 6 = 0 \] Thus, the equation of the tangent line is \( 6x + y - 6 = 0 \). Enjoy your exploration of cubic functions!

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad